Diskresi Pelimpahan Wewenang Tindakan Medik Dari Dokter Kepada Perawat (Studi di Kotawaringin Timur) - Purnawan, Hudi, Dr.Hari Wujoso, Sp..,M.MF (2017)
This research aimed to describe the authority delegation of medical action from doctors to nurses, and the ideal model to overcome the problems of the authority delegation of medical action from doctors to nurses in the East Kotawaringin Central of Kalimantan. This research used socio-juridical methode approach to normative and empirical issues. This type of research is qualitative descriptive. Data was obtained through interviews, observation and documentation. The results of this research revealed that the delegation of medical action from doctors to nurses in the primary health centers in the urban is done in writing, there are the Standard Operating Procedure (SOP), and the form of the authority delegation. Unlike the primary health centers that located in the countryside, the authority delegation is done verbally, there are not the Standard Operating Procedure (SOP), and the form of the authority delegation, even the medical action are mostly done by nurses. While the remote primary health centers the authority delegation is done almost same as the countryside primary health center. An ideal model to overcome the problem that occurred during the authority delegation is by providing an additional medical action competency training to nurses in order that the nurse is able to give the medical action sevice in accordance with the duties and authority that contained in the statute of Nursing.